A Comparative Study of Site-Specific Distribution of Aging-Related Tau Astrogliopathy and Its Risk Factors Between Alzheimer Disease and Cognitive Healthy Brains: The Hisayama Study. Issue 2 (7th December 2021) - Yagita, Kaoru; Honda, Hiroyuki; Ohara, Tomoyuki; Hamasaki, Hideomi; Koyama, Sachiko; Noguchi, Hideko; Mihara, Akane; Nakazawa, Taro; Hata, Jun; Ninomiya, Toshiharu; Iwaki, Toru
Abstract: Knowledge of aging-related tau astrogliopathy (ARTAG) in healthy elderly individuals remains incomplete and studies to date have not focused on the olfactory nerve, which is a vulnerable site of various neurodegenerative disease pathologies. We performed a semiquantitative evaluation of ARTAG in 110 autopsies in the Japanese general population (Hisayama study). Our analysis focused on Alzheimer disease (AD) and cognitive healthy cases (HC), including primary age-related tauopathy. Among the various diseased and nondiseased brains, ARTAG was frequently observed in the amygdala. The ARTAG of HC was exclusively limited to the amygdala whereas gray matter ARTAG in AD cases was prominent in the putamen and middle frontal gyrus following the amygdala. ARTAG of the olfactory nerve mainly consists of subpial pathology that was milder in the amygdala. A logistic regression analysis revealed that age at death and neurofibrillary tangle Braak stage significantly affected the ARTAG of HC. In AD, age at death and male gender had significant effects on ARTAG. In addition, the Thal phase significantly affected the presence of white matter ARTAG. In conclusion, our research revealed differences in the distribution of ARTAG and affected variables across AD and HC individuals.